The Potential of Cellulose as a Source of Bioethanol using the Solid Catalyst: A Mini-Review - Didi Dwi Anggoro; Kamsi Nur Oktavia (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
One of the most important biofuels is cellulose ethanol which is a popular material for bioethanol production. The present cellulosic ethanol production is through the cellulolytic process and this involves the splitting of complex cellulose into simple sugars through the hydrolysis process of the lignocellulose pretreated with acids and enzymes after which the product is fermented and distilled. There are, however, some challenges due to the enzymatic and acid processes based on the fact that acid hydrolysis has the ability to corrode equipment and cause unwanted waste while the enzymatic hydrolysis process requires a longer time because enzymes are costly and limited. This means there is a need for innovations to minimize the problems associated with these two processes and this led to the application of solid catalysts as the green and effective catalyst to convert cellulose to ethanol. Solid catalysts are resistant to acid and base conditions, have a high surface area, and do not cause corrosion during the conversion of the cellulose due to their neutral pH. This review, therefore, includes the determination of the cellulose potential as feedstock to be used in ethanol production as well as the preparation and application of solid catalyst as the mechanism to convert cellulose into fuel and chemicals. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).